Platelet Toll-like receptor and its ligand HMGB-1 expression is increased in the left atrium of atrial fibrillation patients. (March 2018) - Gurses, Kadri Murat; Kocyigit, Duygu; Yalcin, Muhammed Ulvi; Canpinar, Hande; Evranos, Banu; Canpolat, Ugur; Yorgun, Hikmet; Sahiner, Levent; Guc, Dicle; Aytemir, Kudret
Highlights: The most feared sequelae due to atrial fibrillation (AF) are thromboembolic events. In AF, thrombus most commonly originates from left atrium (LA) or LA appendage. We found higher expression of platelet TLR and its ligand in the LA in AF. Our findings suggest immune-mediated platelet activation in LA of AF patients. This may constitute a novel therapeutic target in prevention of thromboembolism. Abstract: Background: Atrial fibrillation(AF) is the most common sustained arrhythmia. Its most feared sequelae are stroke and peripheral thromboembolism due to atrial thrombi formation. Mechanisms underlying the relationship between platelet activation and left atrial thrombi have not been clearly elucidated yet. We aimed to investigate whether immune-mediated platelet activation occurred in AF patients in this cross-sectional study. Methods: Persistent and paroxysmal AF patients who underwent cryoballoon-based AF ablation between March 2015 and July 2016 were included as the patient group. Patients without AF in whom transseptal puncture was performed at the same period for purposes other than AF ablation were included as the control group. Peripheral and left atrial blood samples were obtained for determination of platelet Toll-like receptor(TLR)-2, TLR-4 and high mobility group box-1(HMGB-1) expression levels. Results: A total of 75 subjects (53 patients with AF and 22 control subjects) [mean: 60.33 (SD: 6.14) years, 57.33% male] were included. Left atrial and peripheral TLR-2, 4 and HMGB-1 expression levels were significantly higher in the patient group when compared to the controls. Left atrial platelet TLR-2 and TLR-4 expression and serum HMGB-1 levels were higher in persistent AF patients compared to paroxysmal AF patients. In the patient group, left atrial expression of TLR-2, 4 and HMGB-1 were significantly higher than the peripheral expression levels. Conclusion: Findings of our study suggest evidence for immune-mediated platelet activation in the left atria of AF patients.